3x227yx⋅3y5y4x2=
To solve this problem, we'll follow these steps:
- Step 1: Simplify each fraction separately.
- Step 2: Multiply the simplified fractions together.
- Step 3: Cancel common terms if necessary.
- Step 4: Apply exponent rules for a clearer expression.
Step 1: Simplify each fraction:
The first fraction is 3x227yx. This can be simplified as follows:
3x227yx=327⋅x2yx=9⋅xy.
The second fraction is 3y5y4x2. Simplifying it, we have:
3y5y4x2=35x2⋅y4−1=35x2⋅y3.
Step 2: Multiply the simplified fractions:
9⋅xy×35x2⋅y3=3⋅x9⋅5x2⋅y⋅y3.
Step 3: Simplify again by cancelling out common terms:
=39×5⋅x⋅y1+3=345xy4.
Divide 45 by 3: =15xy4.
Therefore, the product of the two expressions simplifies to 15y4x, which matches choice 1.